Pengembangan Pembelajaran PAI Melalui Inovasi Bahan Ajar Digital di SMK Al-Hidayah Cirebon - Siti Nur ‘Azizah; Abdul Hanan; Ade Irwanto; Ali Murtadlo; Vikria (Indonesian Journal of Islamic Education Studies (INJURIES), 2024)
The development of Islamic Religious Education (PAI) has been a crucial focus in enhancing the educational quality at SMK Al-Hidayah, Cirebon. This research aims to explore and implement innovative digital teaching materials to enrich the PAI learning process within this school environment. The research method used is a qualitative research method to gain insight into the observed phenomenon. Researchers also use a type of case study research that aims to describe and explain the phenomena we studied. The data collection techniques that researchers use are using observation, interviews, and documentation techniques. The findings indicate that the application of digital teaching materials has successfully increased students' interest in learning, broadened access to PAI content, and provided flexibility in the learning process. These findings contribute positively to enhancing the quality of PAI education at SMK Al-Hidayah, Cirebon, and offer guidance for other schools to adopt similar innovations in PAI education. Keywords: Islamic Education Learning; Teaching Materials; Digital